The impact of tourism on municipal solid waste generation: The case of Menorca Island (Spain) - Mateu-Sbert, J; Ricci-Cabello, I; Villalonga-Olives, E; Cabeza-Irigoyen, E (2013)
Tourism can sustain high levels of employment and income, but the sector is a source of environmental and health impacts. One of the most important is the generation of municipal solid waste (MSW). However, there is a lack of studies which quantify how much the tourist population engages in total MSW and separately collected recyclables. The aim of this paper is to estimate the impact of the tourist population on MSW, both total and separately collected, for the period 1998-2010, for the Mediterranean island of Menorca (Spain). We use dynamic regressions models, including data for monthly stocks of tourists. The results show that, on average, a 1% increase in the tourist population in Menorca causes an overall MSW increase of 0.282% and one more tourist in Menorca generates 1.31kgday-1 (while one more resident generates 1.48kgday-1). This result could be useful to better estimate the seasonal population of different regions, since intrannual fluctuation of MSW is used as a proxy measure of actual population (the sum of residents and tourists). Moreover, an increase of 1% in the tourist population causes an increase of 0.232% in separately collected recyclables and an additional tourist generates 0.160kgday-1. One resident selectively collects on average 47.3% more than one tourist. These results can help in the planning of waste infrastructure and waste collection services in tourist areas. © 2013 Elsevier Ltd.